2022
DOI: 10.1016/j.chemosphere.2021.132364
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of medical face masks in domestic and community settings without sacrificing safety: Ecological and economical lessons from the Covid-19 pandemic

Abstract: The need for personal protective equipment increased exponentially in response to the Covid-19 pandemic. To cope with the mask shortage during springtime 2020, a French consortium was created to find ways to reuse medical and respiratory masks in healthcare departments. The consortium addressed the complex context of the balance between cleaning medical masks in a way that maintains their safety and functionality for reuse, with the environmental advantage to manage medical disposable waste despite the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 28 publications
(28 reference statements)
0
36
0
Order By: Relevance
“…Figure 1 a presents a picture of the FFP2 medical mask manufactured by Valmy (Mably, France) and kindly supplied by Grenoble Hospital (see previous work [ 8 ]). Those masks are composed of four layers, which will be characterized before and after irradiation ( Figure 1 b).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 a presents a picture of the FFP2 medical mask manufactured by Valmy (Mably, France) and kindly supplied by Grenoble Hospital (see previous work [ 8 ]). Those masks are composed of four layers, which will be characterized before and after irradiation ( Figure 1 b).…”
Section: Methodsmentioning
confidence: 99%
“…When applicable, the washing conditions were as follows [ 8 ]: 1 h and 12 min at a constant temperature (60 °C), using either pure water or neutral detergent, with “Ultimate mineral” surfactants (1 mL/kg) added, along with “Ultimate Forte” disinfectant based on perchloric acid and hydrogen peroxide (5 mL/kg). Ultimate detergent was chosen because it is commonly used in hospitals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although initially designed as single use, studying the feasibility of the reuse of the medical face masks also appears interesting for both environmental and supply reasons. Some studies have shown that medical face masks are capable of being reused after 10 washing cycles 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%